Pergaulan Bebas Generasi Muda Dalam Perspefktif Hukum Islam (Al-Qur’an) - Jalaludin, Moh.; Azis , Abdul (STAI Publisistik Thawalib Jakarta, 2022)
The phenomenon of free association among adolescents has increased alongside technological advancements and social changes, challenging the ethical principles of Islam and social balance, and impacting moral development and religious order. This study aims to analyze the factors influencing free association among adolescents and its impact on their moral development in the context of Islamic law. The research was conducted using a qualitative library study, collecting data from academic articles. The survey results reveal that free association is increasingly concerning, particularly as technological advances exacerbate moral decline among the younger generation. Various behaviors, such as drug abuse, premarital sex, alcohol consumption, and fighting, are disrupting social and moral order. In Islam, free association is considered haram (forbidden) because it harms physical, mental, and spiritual well-being. The main factors influencing free association include family, technology, and the social environment. The family plays a crucial role in shaping a child's character, while technology accelerates access to harmful content. Islam emphasizes the importance of maintaining personal dignity, guarding one's gaze, and covering one's private parts to protect the younger generation from the harmful effects of free association. In conclusion, free association undermines moral values and social order, making it essential to uphold religious values, family roles, and strict supervision.